Comparing the effect of cup placement between true and false acetabula in total hip arthroplasty in patients with Crowe type 3 dysplastic hip: A randomized clinical trial - Mehdi Motififard; Mohammad Mir Miran Yazdi; Mehdi Teimouri; Saeed Hatami; Moslem Rafiee; Arash Toghyani; Ali Andalib (Journal of Research in Medical Sciences, 2022)
Background: Hip dysplasia is one of the most widespread hip disorders. Total hip arthroplasty (THA) is the preferred treatment in patients with cup placement choices in true or false acetabulum. The objective of this research was to compare the effectiveness of the two mentioned procedures. Materials and Methods: This study was a randomized, open-label, parallel-group clinical trial, in which 46 patients/51 hips with Crowe type 3 dysplastic hip having THA were assigned to two groups: Group 1 – patients who had cup placement in the true acetabulum and Group 2 – patients who underwent cup placement in the false acetabulum. The variables that were evaluated and analyzed included severity of pain using the visual analog scale (VAS), range of motion (ROM), gait ability, the need for repeated joint replacement, and the Harris Hip Score (HHS). Results: Forty-six patients/51 hips were included in the present study. The patients who were evaluated included 30 (65.2%) males and 16 (34.8%) females. The mean age in the population under study was 71.0 ± 10.22, and the mean body mass index of participants was 26.34 ± 2.22 kg/m2. The basic parameters in the two research groups were similar (P > 0.05). There were no significant differences between the two groups in terms of the mean values of VAS and ROM (P > 0.05); however, the mean HHS was significantly higher in the true acetabulum group, 57.90 ± 18.47 versus 48.29 ± 13.80 (P = 0.04). Conclusion: The effectiveness of cup placements both in the true and false acetabula was similar in all of the evaluated variables in terms of clinical outcomes except for HHS which was higher in the true acetabulum group. To further support the results of this research, it is recommended that more research be done on a greater population.